The influence of service quality and perceived risk on repurchase intention with customer satisfaction as mediation - Arifin Firdaus; Malini, Helma; Afifah, Nur; Azazi, Anwar; Fitriana, Ana (Institute of Computer Science (IOCS), 2023)
Nowadays, with rapid technological advances, street food is not just ordinary food sold on the side of the road but has also become the identity of a country. Unfortunately, many business actors pay little attention to the services' quality and the risks involved in their products. This paper aims to identify the influence of service quality and perceived risk variables and their impact on repurchase intention, with customer satisfaction as a mediating variable. The survey was conducted online at locations in Indonesia with 200 respondents. The research results show that Service Quality positively affects Repurchase Intention. Perceived has a negative effect on Repurchase Intention. Customer Satisfaction is proven to mediate the Service Quality and Perceived Risk variables on Repurchase Intention. This offers fresh perspectives for marketing plans that highlight the value of service quality while considering customers' perceived risks to draw domestic and foreign customers to food merchants and establish a new culture.